Improvement of aluminum properties by adding tungsten carbide using powder metallurgy - Majeed, Z. N.; Darweesh, S.Y.; Fadhil, A.A.; Aziz, A. F. A. (Physics and Chemistry of Solid State, 2024)
Powder metallurgy is a usable technique with multiple industrial applications. The first reinforcement material (Al2O3) was used at a constant rate 10wt.%, while the second reinforcement material (tungsten carbide (WC) was used at different rates (0,5,10,15,20wt.%), and the base material is (Al). The three powders were ground together for two hours, and then they were poured into the mold. The compaction process was done with a hydraulic press at (5) tons for one minute. The resulting samples had green density, requiring a thermal sintering process in order to increase their durability and hardness. The sintering process was performed at 560°C for only two hours. Then, structural examinations (scanning electron microscope (SEM) and mechanical examinations (Brinell hardness, compressive strength, and wear) were performed on the sintered samples. The results showed that the best reinforcement rate was 20%, and after thermal sintering, the best Brinell hardness was 146.72 HB, with the highest compressive strength of 45.33MPa, while the lowest wear rate was 1.18×10-8g/cm.